An Analysis of the Implementation and Challenges of the 2024 Indonesian Nutrition Status Survey (SSGI) Validation in East Kalimantan Province - Jamil Anshory; Riska Mayang Saputri G; Indria Pijaryani; Andi Tenri Kawareng; Erri Larene Safika; Ummi Khuzaimah; Leny Eka Tyas Wahyuni; Agustin Putri Rahayu; Lia Kurniasari; Mardiana Mardiana; Sabarinah Sabarinah; Dieta Nurrika; Nastitie Cinintya Nurzihan (Journal of Global Nutrition, 2025)
The Indonesian Nutritional Status Survey (SSGI) is a national tool for monitoring population nutritional status and serves as an evidence base for policy formulation. The accuracy of nutritional prevalence estimates depends on the quality of survey implementation and validation. This study aimed to evaluate the validation process of the 2024 SSGI in East Kalimantan Province, specifically in Samarinda City and Penajam Paser Utara District. A descriptive-evaluative design was applied between July and August 2024, involving households and individuals from validation clusters according to the 2024 sampling design. Data collection included anthropometric measurements, household and individual interviews, field observations, and document reviews, complemented by in-depth interviews with enumerators, validators, and supervisors. Quantitative analysis was performed to calculate procedural deviations, while qualitative thematic analysis was applied to identify recurring challenges related to training adequacy, logistics, supervision, and data quality assurance, with triangulation and inter-rater reliability checks used to strengthen validity. Results show that geographical and accessibility constraints, administrative barriers during sample updating, insufficient technical guidelines, and inconsistent recruitment mechanisms hindered the input stage. At the process stage, deviations were observed in anthropometric measurements, hygiene protocol adherence, and interview completeness, while environmental conditions, limited facilities, and weak coordination influenced the output stage. These findings highlight gaps between standardized protocols and field practices that may compromise data validity. Systemic improvements are required through updated sampling frames, written technical guidelines, practice-based training, layered supervision, and context-specific adaptation strategies to strengthen future national nutrition surveys.